Interplay Between Angiotensin II Type 1 Receptor and Thrombin Receptor Revealed by Bioluminescence Resonance Energy Transfer Assay - Zamel, Isra Al; Palakkott, Abdulrasheed; Ashraf, Arshida; Iratni, Rabah; Ayoub, Mohammed Akli (Frontiers in Pharmacology, 2020)
The key hormone of the renin-angiotensin system (RAS), angiotensin II (AngII), and thrombin are known to play major roles in the vascular system and its related disorders. Previous studies reported connections between AngII and thrombin in both physiological and pathophysiological models. However, the molecular mechanisms controlling such interplay at the level of their receptors belonging to the family of G protein-coupled receptors (GPCRs) are not fully understood. In this study, we investigated the functional interaction between the AngII type 1 receptor (AT1R) and the thrombin receptor (or protease-activated receptor 1 (PAR1)) in human embryonic kidney 293 (HEK293) cells. For this, we used various bioluminescence resonance energy transfer (BRET) proximity-based assays to profile the coupling to the heterotrimeric Gq protein, -arrestin recruitment, and receptor internalization and trafficking in intact cells. The overall dose-response and real-time kinetic BRET data demonstrated the specific molecular proximity between AT1R and PAR1 resulting in their functional interaction. This was characterized by thrombin inducing BRET increase within AT1R/Gq and AT1R/-arrestin pairs and synergistic effects observed upon the concomitant activation of both receptors suggesting a positive allosteric interaction. The BRET data corroborated with the data on the downstream Gq/inositol phosphate pathway. Moreover, the selective pharmacological blockade of the receptors revealed the implication of both AT1R and PAR1 protomers in such a synergistic interaction and the possible transactivation of AT1R by PAR1. Interestingly, the positive action of PAR1 on AT1R activation was contrasted with its apparent inhibition of AT1R internalization and its endosomal trafficking. Finally, BRET saturation and co-immunoprecipitation assays supported the physical AT1-PAR1 interaction in HEK293 cells. Our study reveals for the first time the functional interaction between AT1R and PAR1 in vitro characterized by a transactivation and positive allosteric modulation of AT1R and inhibition of its desensitization and internalization. This finding may constitute the molecular basis of the well-known interplay between RAS and thrombin. Thus, our data should lead to revising some findings on the implication of RAS and thrombin in vascular physiology and pathophysiology revealing the importance to consider the functional and pharmacological interaction between AT1R and thrombin receptors.